O fortalecimento da identidade da mulher negra: caminhos possíveis pela educação e seu impacto em uma perspectiva intergeracional - Dyonisio, Regina de Oliveira (2024)
Historically, black women have had their lives marked by stereotypes related to their bodies and physical features, sexuality, and servitude. However, it is understood that relationships and ways of living in the world and with people change our identities. In other words, there are possibilities of building identities based on dialogue and respect, capable of valuing diversity and the different ways of being and existing in the world. Thus, by taking a racial and gender perspective and focusing on the issue of schooling, we sought to strengthen the identity of black women, emphasizing the possible paths through education and its impact from an intergenerational perspective. This study is qualitative in nature, based on the communicative methodology conceptualized as a tool that understands reality from a communicative perspective, based on the production of scientific knowledge with social impacts. This methodology is characterized by having transformative potential, since it understands that subjects, through communicative action, can transform social contexts, as configured by the proposal of this research. Data analysis included observation of the transformative and exclusionary elements established by the methodology. Thus, we sought to analyze, through the reports of three participating women, which elements enhance and strengthen the identity of black women, and which elements hinder or devalue their identity, considering the instrumental dimension. Because the participants live in different cities, all meetings took place online, via the Google Meet platform. The results obtained from the reports of the three participating black women indicate that black identity is indeed strengthened in higher education and that this space also allows people to recognize themselves as black and see their blackness as positive, thus establishing the instrumental dimension as fundamental. Another aspect is that access to this environment allows black women to increase their self-esteem and empowerment. Also according to the results, dialogue and equality of differences also emerge as something essential for the valorization and positive construction of black identity, being tools for action in the world. In the intergenerational issue, based on data from the black women who participated, it is clear that access to higher education and the acquisition of education of quality resonates in the contexts in which they are inserted, whether as a model of inspiration for other women to fight for the guarantee of rights and access to education, or as a reference for black children. Finally, the aim was to produce excellent quality knowledge and contribute to the academic and scientific debate.